Psoriasis Induced by Isotretinoin in Acne - Brzezinski, Piotr; Borowska, Katarzyna; Chiriac, Anca (Journal of Medicine, 2017)
We described a case of psoriasis possibly resulting from isotretinoin therapy in acne. A 17-year-old patient started treatment with oral isotretinoin (30mg of drug) due to acne vulgaris. After 4 weeks, of treatment, the patient complains for the presence of scattered erythematous plaques and papules. The clinical picture suggested psoriasis (this is also confirmed by histopathological study). The history revealed that the patients mother suffered from psoriasis for 30 years. J MEDICINE January 2017; 18 (1) : 37-38